Informality and corruption - Ajit Mishra; Ranjan Ray (University of Bath, Centre for Development Studies (CDS), 2013)
The paper considers several determinants of the size of the informal sector and explores the implications of corruption. It focuses attention on an issue that has not received much attention before, namely, the link between informality and corruption. We show that corruption affects both the size and composition of the informal sector in a significant manner. While small firms locate in the informal sector to avoid the fixed costs associated with the formal sector, we find that even larger firms might prefer informality because of their superior access to corruption. The paper shows that there is a U shaped relationship between a firm's share of its sales in the informal sector and the scale of its operations. We also show that imperfections in the credit market and wealth inequality are likely to be associated with a larger informal sector. We use a large cross-country firm level survey data to provide supporting evidence. The results of our exercise have considerable policy implications that extend beyond the micro level framework of this study to the wider macro economy.
Keywords: 330; Informal Sector; Shadow economy; Corruption; Inequality